Respuestas
Respuesta dada por:
1
aplicando propiedad de logaritmos:
logab= loga + logb
usamos ello y tenemos
logx + log3 = log24
log(3x)= log 24
entonces 3x= 24
ecuacion simple : x= 24/3 x = 8..... listo :)
logab= loga + logb
usamos ello y tenemos
logx + log3 = log24
log(3x)= log 24
entonces 3x= 24
ecuacion simple : x= 24/3 x = 8..... listo :)
danielaencisozp53itm:
Muchas gracias
Respuesta dada por:
0
✔PROPIEDAD:
![log_{10}(x) + log_{10}(y) = log(xy) log_{10}(x) + log_{10}(y) = log(xy)](https://tex.z-dn.net/?f=+log_%7B10%7D%28x%29++%2B++log_%7B10%7D%28y%29++%3D++log%28xy%29+)
✔OPERANDO:
![log(x) + log(3) = log(24) \\ log(3x) = log(24) \\ 3x = 24 \\ x = 24 \div 3 \\ x = 8 log(x) + log(3) = log(24) \\ log(3x) = log(24) \\ 3x = 24 \\ x = 24 \div 3 \\ x = 8](https://tex.z-dn.net/?f=+log%28x%29++%2B++log%283%29+%3D+++log%2824%29++%5C%5C++log%283x%29++%3D++log%2824%29++%5C%5C+3x+%3D+24+%5C%5C+x+%3D+24+%5Cdiv+3+%5C%5C+x+%3D+8)
✔OPERANDO:
Preguntas similares